El autoestima para el desarrollo socio-emocional de las niñas y niños de 5 años de edad del instituto particular Simón Bolívar de la ciudad de Loja. Periodo 2014-2015 - Malla Soto, Gabriela del Cisne (2016)
This research work, entitled: Self-esteem for socio-emotional development of children from 5 years old Institute of Private Simon Bolivar in the city of Loja. 2014-2015. In which it has been raised as a general objective: to know the ways to use techniques to raise self-esteem through intense field research to influence the socio-emotional development of children from 5 years old. This is a qualitative study, descriptive, which were used scientific, descriptive, deductive and inductive systematic analytic method. Techniques such as the survey of the teacher where they could gather information on the socio-emotional development of girls / os, a test and post-test selfesteem, in order to know how is the self-esteem in girls / os . The research universe consisted of a sample of 13 children, 13 children and 2 teachers giving us a total of 28. It can be concluded that 100% of the surveyed teachers say that the causes of low selfesteem is by discussions at home this is because there is no adequate communication and a good relationship with parents determined so that the child's self-esteem it will be low due to a self-conscious and unsociable attitude that present the results obtained in implementing the post-test, and after the application of manual techniques for socio - emotional development of children / as, was verified that there was an improvement in self-esteem of children, ie within its evolutionary and cognitive development, selfesteem is high self-value very well and the image he has of itself is a positive image, where each of children it is accepted as is; thus we see that their self-esteem as their socio-emotional development are two pillars that must go to the same level of growth.